Multiplier Effect Wisata Halal Masjid Muhammad Cheng Hoo Pandaan dalam Meningkatkan Kesejahteraan Masyarakat di Kabupaten Pasuruan - Inayah, Husnul; Nizar, Muhammad; Fahmul Iltiham, Muhammad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze and understand the role, potential, and multiplier effects of halal tourism at Masjid Cheng Hoo in Pandaan towards enhancing the welfare of the community in Pasuruan Regency. The research methodology employed is qualitative, based on field research. The findings reveal that its historical and cultural value serves as a primary attraction for tourists seeking rich religious and cultural experiences. The potential of halal tourism around the mosque is evident in the increased tourist visits and the growth of the local tourism industry. Furthermore, the study indicates that the development of halal tourism around the mosque has a positive multiplier effect on the welfare of the community in Pasuruan Regency. The growth of the tourism industry creates new job opportunities and enhances household income, while contributing to the development of infrastructure and better public services. These findings underscore the significant economic and social benefits that the development of halal tourism at Masjid Cheng Hoo brings to the local community.